Takaful (Islamic) insurance and its marketability in the Iraqi insurance market: A future study applied in the Iraqi insurance market. - Ismail Mahmoud, Basheer (PT FORMOSA CENDEKIA GLOBAL, 2025)
The insurance sector is one of the largest financial resources that provide the capital funds needed by the economy from the accumulated premiums, beside the banking sector. Therefore, the current study aimed to study the reality of this sector to identify opportunities for developing insurance services. Where we discussed the possibility of applying Takaful insurance in the Iraqi insurance market, According to the basic assumption that there is an opportunity to implement Takaful services in the Iraqi insurance market. The current study reached a number of conclusions, one of which is that Takaful insurance is compatible with the aspirations of Muslim consumers because it works in accordance with Islamic Sharia compared to commercial insurance. At the end the present research provides couples of recommendations one of it was Takaful insurance keeps pace with the needs of insurance customers in Iraq because customers are greatly affected by the religious factor, which is considered one of the biggest factors that affect the spread of commercial insurance services.